Safety and Effects of ILactobacillus paracasei/I TISTR 2593 Supplementation on Improving Cholesterol Metabolism and Atherosclerosis-Related Parameters in Subjects with Hypercholesterolemia: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Khongrum, Jurairat; Yingthongchai, Pratoomporn; Boonyapranai, Kongsak; Wongtanasarasin, Wachira; Aobchecy, Paitoon; Tateing, Suriya; Prachansuwan, Aree; Sitdhipol, Jaruwan; Niwasabutra, Kanidta; Thaveethaptaikul, Punnathon; Phapugrangkul, Pongsathon; Chonpathompikunlert, Pennapa (Nutrients, 2023)
Probiotics have the potential as a multi-target approach to modulate hypercholesterolemia associated with premature atherosclerosis. Various strains of Lactobacillus paracasei have been reported to affect hypercholesterolemia positively. This study aimed to investigate the effects of L. paracasei TISTR 2593 on lipid profile, cholesterol metabolism, and atherosclerosis according to the registration of Thai Clinical Trial Registry as identification number TCTR 20220917002. A total of 50 participants with hypercholesterolemia were randomly and equally assigned to consume L. paracasei TISTR 2593 or a placebo in maltodextrin capsules daily. Biomarkers of lipid profiles, oxidative stress state, inflammatory state, and other biological indicators were examined on days 0, 45, and 90. The results showed that subjects taking the L. paracasei TISTR 2593 could significantly reduce the level of serum low-density lipoprotein-cholesterol (p < 0.05), malondialdehyde (p < 0.001), and tumor necrosis factor-α (p < 0.01). Moreover, L. paracasei TISTR 2593 increased the level of serum apolipoprotein E (p < 0.01) and adiponectin (p < 0.001) significantly. No changes in serum total cholesterol, high-density lipoprotein-cholesterol, triglyceride, total bile acids, and monocyte chemoattractant protein-1 were observed during L. paracasei TISTR 2593 supplementation. Therefore, L. paracasei TISTR 2593 could be an adjuvant probiotic supplement to ameliorate hypercholesterolemia and prevent or delay the development of atherosclerosis.